Analyzing Indomaret Employment in Poka Village, Teluk Ambon District, Ambon City - Difinubun, Megawati; Salakory, Melianus; Lasaiba, Mohammad Amin (Jurnal Pendidikan Geografi Unpatti, 2023)
The workforce refers to the population within the working age range. Employment, including that at Indomaret, is not merely a concern within the community context but also involves specific benefits that the public can obtain. This research employs a descriptive approach, where the author aims to detail the study of employment at Indomaret, located in Poka Village, Teluk Ambon Subdistrict, Ambon City, Maluku Province. The objective is to comprehend the employment development at Indomaret in Poka Village, Teluk Ambon Subdistrict, Ambon City. The research variables encompass the creation of new job opportunities, job prospects, labour absorption, and unemployment reduction. This study was conducted in Poka Village, Teluk Ambon Subdistrict, Ambon City, Maluku Province. The research findings analyze the employment dynamics at Indomaret in Poka Village, Teluk Ambon Subdistrict, Ambon City, which involve providing new job opportunities, job prospects, labour absorption, and unemployment reduction.